1994
DOI: 10.1002/ar.1092400212
|View full text |Cite
|
Sign up to set email alerts
|

Perinotochordal connective sheet of gilthead sea bream larvae (Sparus aurata, L.) affected by axial malformations: An histochemical and immunocytochemical study

Abstract: Lordosis in Sparus aurata originated during embryonic development and was characterized by disorganized connective tissue and muscle bundles. No major differences in connective tissue constituents were seen with respect to normal specimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…For instance, some authors have reported that vertebral deformities may appear during the notochord segmentation and vertebral centrum differentiation processes (Fernández et al 2008, Haga et al 2009). Others have suggested that they are a consequence of dysfunctions in collagen metabolism at notochordal and perinotochordal collagen sheets during early development (Sanatamaría et al 1994). Moreover, vertebral deformities may also occur later in ontogeny (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, some authors have reported that vertebral deformities may appear during the notochord segmentation and vertebral centrum differentiation processes (Fernández et al 2008, Haga et al 2009). Others have suggested that they are a consequence of dysfunctions in collagen metabolism at notochordal and perinotochordal collagen sheets during early development (Sanatamaría et al 1994). Moreover, vertebral deformities may also occur later in ontogeny (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The first effect is buckling failure of the axial skeleton due to an increase in compressive load. Buckling of the axial skeleton has been reported prior to vertebrae formation in sea bream (Sparus aurata) (Andrades et al, 1996;Santamarı´a et al, 1994), but is more commonly correlated with the onset of bony vertebrae formation (Kihara et al, 2002). Interestingly, buckling of the vertebral column in animals without an inflated swim bladder occurs more anteriorly than in fish with an inflated swim bladder (Divanach et al, 1997;Chatain, 1994).…”
Section: Article In Pressmentioning
confidence: 94%
“…7.1 and 7.2). This tissue is composed by an acellular, fibrous elastic sheath, covering a glycosaminoglycan-rich collagenous layer (Grotmol et al, 2005;Sanatamaría et al, 2005), that encloses and constrains the net of chordocytes in the inner core, surrounded by an outer layer of chordoblasts. Using HE, the chordoblast nucleus is stained by haematoxylin while the notochord is clearly stained with eosin, (Fig.…”
Section: The Vertebrae Of Turbotmentioning
confidence: 99%